2015
DOI: 10.1039/c4ta06198e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different lead precursors on perovskite solar cell performance and stability

Abstract: We present the use of halide (PbCl 2 ) and non-halide lead precursors (Pb(OAc) 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 43 publications
1
101
0
2
Order By: Relevance
“…Following this, the sample was dried on a hot plate. 30 Figure 3a clearly shows that the mp-TiO 2 nanoparticles formed an inter-connecting nanoparticulate network. Such a network provides a low grain boundary and a fast electron transport.…”
Section: Resultsmentioning
confidence: 99%
“…Following this, the sample was dried on a hot plate. 30 Figure 3a clearly shows that the mp-TiO 2 nanoparticles formed an inter-connecting nanoparticulate network. Such a network provides a low grain boundary and a fast electron transport.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, optimal film morphology can only be achieved by successfully manipulating the nucleation and growth of the perovskite, thus the control of the crystallization and the kinetics of film formation during deposition and annealing are the keys to the optimization of film morphology. Previous study has been proven that the anions in the lead source determine the kinetics of perovskite crystal growth, which in turn affects the film morphology and device performance [10,13,25]. By choosing a lead source with more volatile byproducts, much smoother films with smaller and fewer pinholes can be obtained due to the reduced annealing temperature and shortened annealing time [13,25].…”
Section: Introductionmentioning
confidence: 97%
“…[42] In a comparative study with other lead precursors, Aldibaja et al showed that films derived from lead acetate resulted in the most homogeneous perovskite films, and a photovoltaic performance comparable to the state-of-the-art. [43] Zhang et al further optimized the use of lead acetate as a precursor and showed that ultrasmooth and pinhole-free perovskite films could be obtained with this method. With the aid of in situ GIWAXS, it was later found that the activation energies for crystallization are dependent on the lead salt, and that they influence the optimum annealing time and temperature.…”
Section: Crystallization From Lead-acetate Precursorsmentioning
confidence: 99%